2003
DOI: 10.1128/mcb.23.15.5234-5244.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Chromatin Landscape Revealed by Patterns of Nuclease Sensitivity and Histone Modification within the Mouse β-Globin Locus

Abstract: In order to create an extended map of chromatin features within a mammalian multigene locus, we have determined the extent of nuclease sensitivity and the pattern of histone modifications associated with the mouse ␤-globin genes in adult erythroid tissue. We show that the nuclease-sensitive domain encompasses the ␤-globin genes along with several flanking olfactory receptor genes that are inactive in erythroid cells. We describe enhancer-blocking or boundary elements on either side of the locus that are bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 63 publications
(71 reference statements)
10
151
1
Order By: Relevance
“…It has been noted that olfactory receptor genes located ∼90 kb upstream of the LCR are orthologous to ones located 40 kb upstream of the murine locus (Bulger et al 2000), indicating that these regions are related. In addition, the murine HS-62.5/ HS-60 element is embedded in a sequence that is similar to a sequence located ∼90 kb upstream of the human LCR (Bulger et al 2003). These observations indicate that the region located ∼90 kb upstream of the human LCR is orthologous to the region located ∼40 kb upstream of the murine locus, suggesting that this region may also interact with the LCR in human cells.…”
Section: Interactions Between Hs5 and Upstream Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that olfactory receptor genes located ∼90 kb upstream of the LCR are orthologous to ones located 40 kb upstream of the murine locus (Bulger et al 2000), indicating that these regions are related. In addition, the murine HS-62.5/ HS-60 element is embedded in a sequence that is similar to a sequence located ∼90 kb upstream of the human LCR (Bulger et al 2003). These observations indicate that the region located ∼90 kb upstream of the human LCR is orthologous to the region located ∼40 kb upstream of the murine locus, suggesting that this region may also interact with the LCR in human cells.…”
Section: Interactions Between Hs5 and Upstream Elementsmentioning
confidence: 99%
“…top, middle, and bottom panels). This region contains three olfactory receptor genes and multiple HS sites (Bulger et al 2003).…”
Section: Interactions Between Hs5 and Upstream Elementsmentioning
confidence: 99%
“…Four genomic regions have been investigated recently in comparable detail to the one presented here: the mouse beta globin locus (19 DHS in 170 kb) (Hardison et al 1997;Bulger et al 2003); the mouse Sprr locus (16 DHS in 260 kb) (Martin et al 2004); the mouse imprinted Igf2/ H19 locus (26 DHS in 130 kb) (Koide et al 1994); and the human imprinted SNRPN locus (eight DHS in 150 kb) (Schweizer et al 1999). The beta globin and Sprr studies also demonstrated a discordance between DHS and ECRs.…”
Section: Evolutionary Conservation Versus Unbiased Approachesmentioning
confidence: 99%
“…subsequently demonstrated to be responsible for this insulator activity of 5 0 HS4 [5]. The human and mouse b-globin loci are also located inside large chromosomal regions of inactive chromatin and are similarly flanked by CTCF-binding sites [17,18]. These were suspected to form a barrier for incoming heterochromatin, but their deletion did not lead to closing or inactivation of the b-globin locus [12,19].…”
Section: Introductionmentioning
confidence: 99%